ANALISIS KERUSAKAN SAMBUNGAN LASAN PADA SISTEM VENTING PRE AIR COOLER DI LINGKUNGAN EKSPLORASI DAN PRODUKSI GAS ALAM - Kemal Arthur Uktolseja; Margono Sugeng (Bina Teknika, 2017)
The purpose of this study was to determine the cause of damage to the welded joints in the spool pipe on the pre-cooler air venting system in the natural gas exploration and production environment in the form of crack defects. The analysis was done by taking field data in the form of operational data and chemical content of fluid served, visual observation, chemical composition test with Optical Emission Spectrocopy, Hardness Testing using Rockwell scale B, Micro observation and makrophotograpy, Metalographic observation, microhardness testing using Vickers test plane, Observation of macro fracture surface using Scanning Electron Microscope. Based on the results of the tests and observations, it shows that the main cause of the damage is the brittle crack caused by the welding performance made possible by the use of higher current than required and rapid cooling of the welding of the thin material.